Application of the Fuzzy Delphi Method to Organisational Leadership Competencies for Educational Middle Leaders: Aplikasi Fuzzy Delphi Method Terhadap Kompetensi Kepimpinan Organisasi Bagi Pemimpin Pertengahan Pendidikan - Beram, Sukor; Awang, Marinah; Ismail, Ramlee; Noor, Norzalina (Management Research Journal, 2021)
Quality education is highly dependent on the level of teacher professionalism and the effectiveness of educational leadership. Many studies on educational leadership focus on the leadership of Principals and Head Teachers, rather than examining the roles of middle leaders who are also the backbone of educational leadership. Thus, this study aims to obtain expert consensus on the construct of organisational leadership competencies for intermediate leaders in matriculation colleges using the Fuzzy Delphi Method (FDM) approach. An instrument containing constructs and a list of elements was submitted to a total of 30 experts from various fields and backgrounds to obtain expert panel agreement. The findings of this study indicate that the expert panel agreed with the constructs and elements of organisational leadership competencies presented. The threshold values ​​of all 15 elements tested met the condition of d≤0.2, obtained expert agreement exceeding 75% with values ​​ranging from 86.7% to 100% agreement, and exceeded the requirement of alpha cut values ​​exceeding 0.5 (α-cut≥0.5) with values ​​ranging from 0.870 to 0.929. The defuzzification process carried out through FDM has also rearranged all the elements based on the ranks agreed by the experts. This study successfully presents a new construct by taking into account the important elements in the context of organisational leadership competencies involving middle leaders.